DESIGN OF SUSTAINABILITY-BASED MULTIFUNCTIONAL FURNITURE TO ENHANCE THE FLEXIBILITY OF COLLABORATIVE SPACES AT THE“WORK UNUSUAL” COFFEE SHOP - Wahyu Dwi Utami; Santi Salayanti; Agustinus Nur Arief Hapsoro (Adisam Publisher, 2026)
This study discusses the design of multifunctional furniture at the “Work Unusual” coffee shop, which features collaborative spaces with a high intensity of collaboration and requires spatial flexibility. The main problem arises from users’ needs for adaptive, ergonomic, and sustainable furniture, while the existing facilities have not fully supported the variety of community activities. This study aims to identify user needs, evaluate existing conditions, and formulate alternative furniture designs that are more functional and responsive to collaborative activities. The research employs an exploratory mixed-methods approach, in which the qualitative stage serves as the foundation for an in-depth understanding of the phenomenon. Data were collected through observations, interviews, questionnaires, and documentation to explore user experiences related to functionality, flexibility, and sustainability aspects of the furniture used at “Work Unusual.” The collected data were then used to develop quantitative instruments, which were analyzed using the Simple Additive Weighting (SAW) method to determine the most optimal design alternative. The design process follows the stages of design thinking as a systematic approach to solving design problems. The results indicate that users require furniture that is multifunctional, flexible, and compatible with various activities such as workshops, bazaars, and dine-in activities. The SAW analysis shows that functionality, flexibility, sustainability, and aesthetics are the main determining factors in user preferences. In addition, the study finds that sustainable materials and modular designs have the greatest potential to improve spatial efficiency. Therefore, multifunctional furniture designed with functional, flexible, and sustainability principles can contribute to optimizing collaborative spaces at “Work Unusual.” This study provides comprehensive design recommendations and can serve as a reference for the development of adaptive furniture in other collaborative spaces.